Maqom dan Ahwal: Makna dan Hakikatnya dalam Pendakian menuju Tuhan - Asnawiyah Asnawiyah (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2014)
Religious teachings is important aspect for every person. The meaning of religious life for every adherent is to reach the highest degree before one‟s God. There are many ways to to perfect human‟s spirit in order to reach the highest degree. In Islam, human‟s degree is different from one to another before the Creator. The degree is called maqam, which illustrates one position or degree. To reach the highest maqam, one has to pass through many stages. In the order side, Islamic mysticism knows the term of ahwal. Dissimilarly from maqam, ahwal is God‟s bestow to someone without need to great efforts. Since maqam is a position, which has to be reached by making serious efforts, so the harder one sacrifices to pass through each maqam stage, the nobler the one before the God.